2017
DOI: 10.12991/marupj.323588
|View full text |Cite
|
Sign up to set email alerts
|

HPLC Assay Method Development and Validation for Quantification of Capecitabine in Tablets and Forced Degradation Samples

Abstract: A simple, rapid, accurate and stability indicating RP-HPLC method was developed for the determination of Capecitabine in pure and tablet dosage form. The mobile phase consisting of 0.1% aqcetic acid, methanol and acetonitrile in the ratio of 35:60:5 v/v. The Inertsil ODS (octadecyl silane), C18, 3V, 250 x 4.6 mm, 5µm with UV detection 304 nm was used. The retention time was found to be 6.4 minutes. The method was statistically validated for accuracy, linearity, precision, robustness, specificity and range. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The assays were performed in triplicate, and the results for both analyzed cell lines are presented in Table 3. The UFLC method used in this research has been employed in other studies to determine the concentration of CAP in samples obtained from dissolved tablets [13,18,19], and in plasma samples [4,20,21]. In all of them, UFLC proved to be a suitable method with proven e ciency for determining the concentration of the prodrug CAP in various samples.…”
Section: Determination Of Thymidine Phosphorylase Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The assays were performed in triplicate, and the results for both analyzed cell lines are presented in Table 3. The UFLC method used in this research has been employed in other studies to determine the concentration of CAP in samples obtained from dissolved tablets [13,18,19], and in plasma samples [4,20,21]. In all of them, UFLC proved to be a suitable method with proven e ciency for determining the concentration of the prodrug CAP in various samples.…”
Section: Determination Of Thymidine Phosphorylase Activitymentioning
confidence: 99%
“…Moreover, in many previously described studies, it is known that the prodrug CAP is converted into 5-FU through at least three metabolic steps after intestinal absorption, namely: starting with the action of hepatic carboxylesterases that convert CAP into 5'-DFCR, which is then converted to 5'-DFUR by cytidine deaminase present in high concentrations in the liver, plasma, and tumor tissue; and nally, 5'-DFUR is converted into the active drug 5-FU by the action of thymidine phosphorylase, which is found in higher quantities in solid tumors compared to adjacent normal tissues, and thus exerts its cytotoxic effect on cancer cells [20,28]. However, from the results obtained in this study, it is observed that the metabolic pathway for converting CAP to 5-FU may not be exclusively dependent on the action of hepatic carboxylesterases, suggesting that these enzymes may also be present in tumor cells, or that there may be other pathway(s) in tumor cells capable of promoting the conversion of CAP to 5-FU, or even to another metabolite(s) of CAP that possess signi cant cytotoxic effects on MCF-7 and MDA-MB-231 cell lines.…”
Section: Determination Of Thymidine Phosphorylase Activitymentioning
confidence: 99%
“…It acts as a prodrug that was triggered by the enzyme thymidine phosphorylase to act on tumor cells by its cytotoxic moiety, and fluorouracil (FU). The active moiety of capecitabine said to be "targeted" against the cancerous cells [2]. The elimination half-life of both capecitabine and 5-FU is about 0.89 h, with more than 70% of the administered dose recovered in urine, largely as a metabolite of 5-FU the absolute bioavailability of capecitabine is 42%.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid chromatography is a rapid and simple method for studying drugs in pharmaceutical and clinical samples, but they need expensive devices and high purity solvents, which can restrict their use . Also the electrochemical methods can be seen in the literature because of their comfortable properties such as short analysis time, low cost, and sensitivity.…”
Section: Introductionmentioning
confidence: 99%